Critical Factors Affecting the Innovation Activities of Businesses: Evidence from Binh Dinh Province, Vietnam - Nguyen Thi Lệ Hằng; Ngoc Toan Pham; Vu Phuong Linh Dao; Thi Thanh Thuy Ngo; and Thi Thanh Binh Le (My University, 2020)
Critical Factors Affecting the Innovation Activities of Businesses: Evidence from Binh Dinh Province, Vietnam
Keywords: Innovation Activities; Critical Factors; Binh Dinh